(untitled) (Bangladesh Agronomy Journal, 2017)
An on farm field experiment was conducted to evaluate locally improved aman rice varieties in terms of nitrogen use efficiency and grain yield in southern region of Bangladesh. The treatments were: i. deep placement of urea (UDP) before panicle initiation stage and ii. farmers practice (FP/control). The locally popular rice varieties were used as planting materials. Higher panicles m-2 and grains panicle-1 was obtained from UDP application compared to FP. Nitrogen fertilization increases grain and straw nitrogen content significantly. Application of urea before panicle initiation stage gave considerable higher grain yield in all cultivated varieties. Cultivated aman varieties produced 2.0 to 2.5 t ha-1 grain without application of N fertilizer. But, cultivated local variety Razashail, Kutiagoni, Sadachikon, Sadapajam, Lalmota and Sadamota gave 3.0 to 3.5 t ha-1 grain in tidal prone areas with UDP. Hence, application of urea gave yield advantage by 0.5 to 1.0 t ha-1. The highest internal, agronomic, recovery and physiological efficiency; nitrogen harvest and grain yield efficiency index was obtained from Kutiagoni, Lalpayka, Sadachikon, Sadapajam, Moulata and Lalmota. Based on the yield and nitrogen fertilizer use efficiency, it could be concluded that UDP before panicle initiation stage is an effective option of urea application for rice cultivation in tidal prone areas. Bangladesh Agron. J. 2016 19(2): 39-49